Grants Scheme : 2007 Report. (Carrick Institute for Learning and Teaching in Higher Education, 2007)
The Grants Scheme enables the Carrick Institute for Learning and Teaching in Higher Education to realise its designated responsibility to provide grants for academics and professional staff to investigate, develop and implement innovations in learning and teaching, and to develop leadership capabilities. This report provides information about the scheme's activities in 2007.